Science fiction tells us nothing about the future - Podruczna, Agnieszka; Sikora, Agnieszka (No Limits, 2021)
Dr. Agnieszka Podruczna conducts research on science fiction in English-language postcolonial literature, however, she deals with specific SF literature – not only with works related to North America, but also written by non-white women; authors who come from minorities and diasporic or indigenous communities. In dealing with these works, Dr. Podruczna describes themes around which sci-fi specifically revolves, such as physicality, slavery, displacement, the search for a home, and the rifts between two worlds that usually put human beings in situations of decisive choice.